Research on the Mechanical Integrity of Low-Density Cement Mortar - Renjun, Xie; Zhiqiang, Wu; Xiaowei, Cheng; Xiucheng, Ni (Frontiers in Materials, 2022)
Poor mechanical integrity of cement sheaths during the production of oil and gas wells may cause air channeling and water channeling issues in the wells, leading to severe safety problems, and adversely affecting the safety and efficiency of the oil and gas resources production. This article focuses on a low-density cement slurry system with added floating beads. The compressive strength and flexural strength of cement stones, the mechanical integrity of cement rings, and triaxial mechanical properties were assessed. The optimal dosage of floating beads and the evolution of the cement stone’s mechanical properties and deformation ability were discussed. Bonding strengths of the first and the second interfaces were evaluated using the shrinkage test results of the cement mortar. Finally, the microscopic mechanism of the change in mechanical properties was analyzed by scanning electron microscopy. The results showed that the cement mortar exhibited the best compressive strength, mechanical integrity, and deformability after blending with 15% floating beads. At the same time, the volume shrinkage of the cement mortar mixed with 15% floating beads was the smallest, only 0.00667%, plausibly indicating good bonding with a casing and the formation to reduce the occurrence of gas channeling. Finally, the microscopic test of the cement mortar showed that the bonding between floating beads and cement was not tight, so internal cracks in the cement easily developed along the bonding part of cement and floating beads. The more floating beads were mixed, the more likely was cement mortar destroyed.